2012
DOI: 10.1021/ac302022d
|View full text |Cite
|
Sign up to set email alerts
|

Ionization, Transport, Separation, and Detection of Ions in Non-Electrolyte Containing Liquids

Abstract: Liquid phase ion mobility spectrometry (LPIMS) has the potential to be miniaturized such that it can be incorporated into chip based technology, providing higher performance in terms of both detection sensitivity and resolving power than is currently available by other separation technologies such as gas phase IMS, chromatography, or electrophoresis. This work presents modeling, simulation, and experimental investigations to characterize the mobility of ions in a liquid phase. This study included the ionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[106][107][108][109][110][111][112][113] One method of comparing their efficiency is to use resolving power/length (R p /L). 114 Babis et al 106 obtained a R p /L of 3.2 cm −1 (for a length L of 4.65 cm and a R p of 15), although different in design Xu et al 112 obtained a R p /L of 3.4 cm −1 (for a length L of 3.50 cm and a R p of 12). As the length L of an IMS is reduced, the primary limitation to resolving power is the limit on producing effective ion pulses to inject into the IMS.…”
Section: Resolution and Resolving Powermentioning
confidence: 98%
See 1 more Smart Citation
“…[106][107][108][109][110][111][112][113] One method of comparing their efficiency is to use resolving power/length (R p /L). 114 Babis et al 106 obtained a R p /L of 3.2 cm −1 (for a length L of 4.65 cm and a R p of 15), although different in design Xu et al 112 obtained a R p /L of 3.4 cm −1 (for a length L of 3.50 cm and a R p of 12). As the length L of an IMS is reduced, the primary limitation to resolving power is the limit on producing effective ion pulses to inject into the IMS.…”
Section: Resolution and Resolving Powermentioning
confidence: 98%
“…Nevertheless, several recent attempts have been made to miniaturize the IMS devices 106113 . One method of comparing their efficiency is to use resolving power/length ( R p /L ) 114 . Babis et al .…”
Section: Data Key Figures Of Meritmentioning
confidence: 99%
“…The investigation of ions in liquids is of considerable interest for the understanding of interactions in bulk liquids 1,2 as well as for applications, for examples ionic liquids [3][4][5] or chemical analysis. 6,7 Attractive interaction between ions and the solvent liquid gives rise to the formation of clusters whose size can be elucidated by measuring their mobility. The modelling of ion mobility is nevertheless a great challenge since fluid properties have to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Since the diffusion coefficient of ions decreases by three 20 [11,14,21], ions travel much more slowly in liquid than they do in gas. This opens the door to a smaller instrument that Fig.…”
Section: Liquid Phase Systemmentioning
confidence: 99%
“…The voltage across the drift region was 2580 V. Lamabadasuriya, et al, have reported preliminary experimental results with such a device [20]. We perform our analysis with an analyte of mass 167 u and K = 2.55 × 10 −3 cm 2 /Vs.…”
Section: Liquid Phase Systemmentioning
confidence: 99%